Arbitrage, Error Correction, and Causality: Case of Highly Traded Agricultural Commodities in India - Kaura, Ruchika; Kishor, Nawal; Rajput, Namita (Indian Journal of Finance, 2019)
India is an agriculture-dominated country and futures trading in commodities has emerged as a mode to protect the farmers and traders from price fluctuations and to relieve them from the trouble of maintaining stocks. However, mispricing between futures and spot markets of commodities has persisted from time to time due to market inefficiencies, which are taken care by rational investors and arbitrageurs present in the market. The study aimed to examine the speed, magnitude, and significance of error correction in the presence of arbitrage opportunities and the causality relationship between the spot and the futures markets of selected highly traded agricultural commodities namely, cardamom, cotton, crude palm oil, and mentha oil traded on the leading commodity exchange of India, that is, MCX. The results of vector error correction model provided empirical evidence that there existed significant error correction and causality between the futures and spot prices of selected agricultural commodities in India. Even though the futures and spot prices of these commodities were co-integrated in the long run, but in the short-run, there arose a disequilibrium resulting in exploitable arbitrage opportunities. Trading by the arbitrageurs in these markets leads to significant error correction, thereby bringing the markets into equilibrium again. Also, bi-directional causality between the markets was observed for all commodities with futures markets Granger causing spot markets more strongly. The knowledge of existence of arbitrage opportunities and information about the error correction is valuable for farmers, traders, and organizations occupied in producing, processing, and marketing of commodities to hedge their market risk and gain profits.